Faktor-Faktor Fundamental Keuangan Perusahaan dan Pengaruhnya Terhadap Return Saham Perusahaan Kelompok Jakarta Islamic Index Tahun 2011-2016 - Fitria Husnatarina; Rosel Rosel; Faishal Rona Akhmad (The Indonesia Capital Market Institute, 2020)
Purpose - This research was conducted in order to examine the influence of corporate financial fundamental factors (CR, ROA, NPM, DER, EPS, PBV, PER and TATO) on the 2011-2016 Jakarta Islamic Index group company stock returns. Methods - The analysis technique used is the Random Effect method with Generalized Least Square as an estimation tool. The sampling technique used was purposive sampling with the criteria that the company always listings and is consistent in the Jakarta Islamic Index from 2011-2016. The data in this study were obtained secondary with a total sample of 15 companies. The test hypotheses used are t-statistics and F-statistics at the 0.05 significance level. Finding - The results showed that PER and EPS had a statistically significant negative effect on stock returns, while CR, NPM, DER, EPS, PBV and TATO had no statistically significant effect on stock returns. The results of this study indicate that the fundamental factors are valuation ratios (EPS and PER) used by investors to predict the JII group stock returns in 2011-2016.